Intranasal insulin enhances resting-state functional connectivity in Type 2 Diabetes - Zongpai Zhang; Vera Novak; Peter Novak; Christos Mantzoros; Long Ngo; Vasileios Lioutas; Weiying Dai (PLoS ONE, 2025)
Type 2 diabetes mellitus (T2DM) affects cognition and resting-state functional connectivity (rsFC). Intranasal insulin (INI) has emerged as a potential treatment for T2DM-related cognitive decline. We aimed to evaluate the effect of INI treatment on rsFC with medio-prefrontal (mPFC) and left/right hippocampus (lHPC/rHPC), and their relationship with the cognition, hemoglobin A1c (HbA1c), and homeostatic model assessment of insulin resistance (HOMA-IR) and walking speed. An MRI sub-study of the MemAID trial was conducted, involving a 24-week treatment with either intranasal insulin or placebo. Blood oxygen level-dependent (BOLD) functional MRI (fMRI) images were acquired on eighteen DM subjects at baseline and eleven DM subjects (eight DM-INI patients and three DM-Placebo) at the end-of-treatment. Compared to DM-Placebo treated subjects, DM-INI patients showed increased mPFC-postcentral rsFC, lHPC-frontal rsFC, lHPC-postcentral rsFC, rHPC-frontal rsFC, and lHPC-mPFC rsFC (p < 0.05). The decreased HOMA-IR, which was observed in the MemAID trial, was associated with increased mPFC-basal ganglia rsFC (p < 0.05). This sub-study provides insights into potential mechanisms of INI effects on rsFC that require validation in a larger trial.